2023
DOI: 10.1167/iovs.64.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Myo/Nog Cells Give Rise to Myofibroblasts During Epiretinal Membrane Formation in a Mouse Model of Proliferative Vitreoretinopathy

Abstract: Purpose Myo/Nog cells are the source of myofibroblasts in the lens and synthesize muscle proteins in human epiretinal membranes (ERMs). In the current study, we examined the response of Myo/Nog cells during ERM formation in a mouse model of proliferative vitreoretinopathy (PVR). Methods PVR was induced by intravitreal injections of gas and ARPE-19 cells. PVR grade was scored by fundus imaging, optical coherence tomography, and histology. Double label immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 67 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…lineage [70]. We concluded that the death of human RPE cells was the likely stimulus for proliferation and migration of Myo/Nog cells and their engulfment of cell corpses [70], as occurs in other tissues, including the lens [68].…”
Section: Additional Behaviors Of Myo/nog Cells In the Lens And Relate...mentioning
confidence: 86%
See 4 more Smart Citations
“…lineage [70]. We concluded that the death of human RPE cells was the likely stimulus for proliferation and migration of Myo/Nog cells and their engulfment of cell corpses [70], as occurs in other tissues, including the lens [68].…”
Section: Additional Behaviors Of Myo/nog Cells In the Lens And Relate...mentioning
confidence: 86%
“…The next phase of our exploration of Myo/Nog cells involved characterizing their behaviors in normal and diseased tissues of adult mammals. Similar to the chick embryo, Myo/Nog cells are present in low numbers in all adult tissues and organs analyzed thus far, from mice to humans [ 16 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Within the eye, Myo/Nog cells are residents of the lens, cornea, ciliary body, retina and choroid [ 16 , 62 , 63 , 66 , 67 , 68 , 70 , 71 , 72 ] ( Figure 4 ).…”
Section: Myo/nog Cells In the Adult Eyementioning
confidence: 99%
See 3 more Smart Citations